Survival of an Antarctic cyanobacterial mat under Martian conditions - Martin-Andres, Irene; Sobrado, Jesús; Cavalcante, Erika; Quesada, Antonio (Frontiers in Microbiology, 2024)
Antarctica is one of the most outstanding analogues of Mars and cyanobacterial mats are considered one of the most resilient biological consortia. The purpose of this work is to find out what is the effect of the Martian conditions on an Antarctic cyanobacterial mat. We exposed an Antarctic microbial mat to Mars conditions in a simulating chamber (MARTE) for 15 days and investigated the variations in the consortium by the use of rRNA 16S gene expression as an indicator of the biological activity. Metabarcoding using the V3-V4 regions of rRNA 16S gene was used to determine the succession of the active members of the microbial consortium during the experiment. Results showed that the microbial mat, far from collapsing, can survive the stringent conditions in the simulating chamber. Different behaviours were displayed depending on the metabolic capabilities and physiological characteristics of every taxon. The main conclusion is that the Martian conditions did not impair growth in some of the groups, and thus the investigated Antarctic community would be able to survive and even prosper in a Martian environment at least during the short experimental period although elements of the community are affected in different ways. 1 32. Qiime2docs. Natively installing QIIME 2. 2021.